Comparison of Digital Elevation Model (DEM) from consumer grade drone with shallow-water bathymetry at Redang Island Marine Park, Terengganu - Mohd Jinah, Muhammad Idzham Helmi; Ahmad, Zuhairi; Azmi, Aiman Hisyam; Zulkifli, Muhammad Amiruddin; Mustapa, Mohd Zaini; Yang Amri, Affendi; Lean Sim, Jillian Ooi; Kassim, Zaleha; Zakariya, Razak; Chan, Albert Apollo; Rosli, Muhammad Khairulanwar (2020)
The most common method of obtaining shallow-water bathymetry usually by using single beam echosounder. Recent technology shows that consumer grade drone not only capable to capture aerial images, but also provide DEM of terrain and land area. However, there are less studies and information regarding shallow-water bathymetry derived from consumer grade drone DEM. Thus, this study compared the DEM produced by consumer grade drone with the bathymetry from Single Beam Echosounder (SBES) for shallow-water area in Redang Island Marine Park. The DJI Phantom 4 with Zenmuse X3 camera (RGB) have been used to obtain aerial images with elevation data. The drone fly with automated DroneDeploy application during a standardized time ranged between 8AM to 10AM and 4PM to 6PM, in order to avoid excessive sun glint. The bathymetry survey has been conducted using SBES Hummingbird 581iHD Down ImagingTM. The data from drone and SBES were processed into DEM using DroneDeploy Proprietary Map Engine and Hypack Max 2014. The DEM data from drone and SBES extracted at 24 transect locations and compared statistically. The result indicates the data at most shallow level (0m to -1m) have the highest value of R2 (0.3335) and lowest RMS error (0.082), in comparison with depth more than 1m. Therefore, the bathymetry derived from consumer grade drone DEM, based on RGB sensor is not suitable to be used for safety navigation mapping, especially for depth greater than 1m. However, it can be applied for other coastal study purposes, such as shoreline monitoring.